Pengaruh dari Kualitas Layanan dan Presepsi Harga Terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan Sebagai Variabel Mediasi : Study Kasus pada Coffee Shop Bajawa di Bekasi - Nova Yudha Andriansyah Putra; Ida Zuniarti; Lia Mazia (Dharma Ekonomi, 2025)
This study highlights Bajawa Coffee Shop in Bekasi as the main subject in examining the factors that influence customer loyalty. This study aims to analyze the effect of service quality and price perception on customer loyalty, with customer satisfaction as a mediating variable. Service quality refers to the extent to which the service provided is able to meet customer expectations, while price perception is the customer's assessment of the economic value of the product or service received, which is influenced by costs, market demand, and business strategy. Customer satisfaction is a subjective evaluation of the experience of using a service, which reflects how well customer expectations are met by actual performance. This satisfaction plays an important role in building long-term relationships between customers and companies, and has a major impact on loyalty, brand reputation, and business sustainability. Customer loyalty itself is defined as a commitment to continue choosing and recommending a particular product or service, despite offers from competitors. In the context of increasingly tight competition in the cafe industry and the increasing trend of coffee consumption, understanding the factors that shape loyalty is very important. This study uses service quality and price perception as independent variables, customer satisfaction as a mediating variable, and customer loyalty as a dependent variable. The results of this study are expected to contribute to the development of more effective business strategies in retaining customers at the Bajawa Bekasi Coffee Shop.